The Interplay of Public Health, Politics, and Economics in COVID-19 Border Control Strategies: A Comparative Study of Brunei Darussalam, UK, China, Germany, and Australia - Lee, Brice Tseen Fu; Asihaer, Ayidana; Sims, Juan Pablo; Ali, Salman (Unnes Political Science Journal, 2023)
This study investigates the effectiveness of border control in containing the spread of COVID-19. Through a literature review and discourse analysis, the study examines the pandemic response of China, the UK, Brunei Darussalam, Australia, and Germany, with a focus on their border control policies. The data collected suggests that countries with closed borders were more successful in dealing with the COVID-19 pandemic in terms of health statistics, such as the prevention of infection, hospitalization cases, and death rates. Effective domestic public health measures, including mask mandates and social distancing, were also found to be critical components of successful pandemic containment protocols. However, the study also highlights the impact of domestic and international relations and political perceptions on shaping each government’s pandemic response. The role of the economy was identified as the biggest factor contributing to the government decision to close their borders, with regime type considered to a certain extent as it allows for less pushback towards policy changes. Overall, the study suggests that a combination of effective domestic public health measures and border controls is critical to containing the spread of COVID-19.